Analisis SWOT (Strengths, Weakness, Opportunities, Threats) Model Pendidikan Karakter dalam Pembelajaran Pendidikan Agama Islam Berbasis Kecakapan Abad 21 - Afifah Zahro'; Moh. Khusnuridlo; Syamsul Anam; Zainuddin Al Haj Zaini; Abd. Muhith (PAKAR Pendidikan, 2023)
Rapid development in the 21st century affects various fields of human life and has positive and negative impacts. One of the negative impacts is the problem of children's character. Research on character education in the 21st century through PAI learning is very important to overcome this problem. Previous studies have discussed character building through PAI in the 21st century, but this study focuses more on the discussion of the details of the PAI learning process that takes place. This research uses a qualitative research method with a text study research type whose data collection is by collecting various texts of information from articles, proceedings, and other relevant literature. This study aims to describe the efforts to implement character education in PAI learning with various skills discussed by the 21st century and the results of the analysis of strengths, weaknesses, opportunities, and threats. The results of this study are: 1) Character education efforts through PAI learning apply 21st-century skills in the form of literacy and problem-based learning. 2) The strength is PAI as a subject with the main mission of shaping the character of students; the weakness is that PAI is a subject that is often considered a formal subject only, the opportunity is PAI as a compulsory subject at every level of education, and the threat is the ease of information in the 21st century making the presence of radicalism. Character education efforts through PAI learning with literacy and problem-based learning in the 21st century can be a reference for educators and researchers, but in its implementation, there are strengths, weaknesses, opportunities, and threats.